Funções trigonométricas complexas: uma abordagem voltada para o Ensino Médio - Nascimento, Franciel Araújo do (2015)
This dissertation present a study of trigonometric functions with complex variable with a focus on basic education. The motivation comes from the fact that it has given little importance to complex numbers in school, since the current approach is restricted the settings, properties and theoretical exercises and immediate application, as shown, for example, the NCP’S. Presents a approach of the complex numbers through matrix, without losing sight of the way in which those numbers are presented, as ordered pairs, in the basic mathematic. It then presents the functions with complex variables, their properties and consequently a study of sine functions, cosine, tangent, cotangent, secant and cosecant with complex variable. Some comparisons between real and complex functions are performed. Finally, we present an application of complex trigonometric functions in physics.